A comprehensive guide to the prostate : eastern and western approaches for management of BPH - Chughtai, Bilal (Academic Press, an imprint of Elsevier, 2018)
"A Comprehensive Guide to the Prostate: Eastern and Western Approaches for Management of BPH provides a multidisciplinary approach to BPH and male voiding dysfunction, presenting comprehensive guidance on management. With an equal focus on traditional, complementary and alternative medicine, and a look at novel technologies, a complete understanding of the BPH disease process is revealed. Abstracts and references in every chapter make the connection between research and practice. Perfect for researchers and urologists, this must-have reference provides what is needed to understand BPH and male voiding dysfunction. Presents a comprehensive and multidisciplinary approach on BPH and male voiding dysfunctionGives equal focus to traditional, complementary and alternative medicine Provides access to videos of procedures using the various treatment modalities covered in the book"--